Mechanisms of liver fibrosis in metabolic syndrome - Wajahat Mehal (eGastroenterology)
The understanding of the mechanisms of liver fibrosis has been dominated by models in which chronic hepatocellular injury is the initiating step as is seen with viral infections. The increased prevalence of the metabolic syndrome, and the increases in liver fibrosis due to metabolic syndrome driven non-alcoholic steatohepatitis (NASH), has made it a priority to understand how this type of liver fibrosis is similar to, and different from, pure hepatocellular injury driven liver fibrosis. Both types of liver fibrosis have the transformation of the hepatic stellate cell (HSC) into a myofibroblast as a key step. In metabolic syndrome, there is little evidence that metabolite changes such as high levels of glucose and free fatty acids are directly inducing HSC transdifferentiation, however, metabolite changes may lead to reductions in immunomodulatory and hepatoprotective molecules such as lipoxins, resolvins and Interleukin (IL)-22. Cells of the innate immune system are known to be important intermediaries between hepatocellular damage and HSC transdifferentiation, primarily by producing cytokines such as transforming growth factor-β (TGF-β) and platelet derived growth factor (PDGF). Resident and infiltrating macrophages are the dominant innate immune cells, but others (dendritic cells, neutrophils, natural killer T cells and mucosal-associated invariant T cells) also have important roles in inducing and resolving liver fibrosis. CD8+ and CD4+ T cells of the adaptive immune system have been identified to have greater profibrotic roles than previously realised by inducing hepatocyte death (auto-aggressive CD8+T) cells and cytokines producing (TH17 producing CD4+T) cells. Finally, the cellular networks present in NASH fibrosis are being identified and suggest that once fibrosis has developed cell-to-cell communication is dominated by myofibroblasts autocrine signalling followed by communication with cholangiocytes and endothelial cells, with myofibroblast-hepatocyte, and myofibroblast-macrophage signalling having minor roles. Such information is essential to the development of antifibrotic strategies for different stages of fibrosis.